2008
DOI: 10.1530/eje-08-0033
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of IGF-binding protein 2 in patients with non-seminomatous germ cell cancer: correlation with tumor markers α-fetoprotein and human chorionic gonadotropin

Abstract: Background/aims: Alterations of the IGF system have been described in several different types of cancer. However, no information is available about the role of the IGF system in patients with nonseminomatous germ cell cancer. Methods: Free IGF-I, IGF-II, acid-labile subunit, and IGF-binding proteins (IGFBPs) 1-4 were analyzed by specific RIAs in 32 patients with untreated non-seminomas and compared with IGFBP levels of 38 healthy controls. Serum IGFBPs were analyzed by western ligand blotting (WLB) and immunob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Here, we have identified active IGF1R signalling and have demonstrated that this plays a key role in maintaining nonseminoma cell viability and can also contribute to cisplatin resistance. Our finding of phosphorylated IGF1R in nonseminoma cells and high IGF1R expression levels in patient samples fits with previous observations noting high serum levels of IGF-2 and IGFBP2 in nonseminoma patients that reduced after treatment [42]. Similarly, the proportion of cleaved IGFBP3 (which promotes proliferation in breast cancer [43]) is greater in nonseminoma patients and declines upon response to treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Here, we have identified active IGF1R signalling and have demonstrated that this plays a key role in maintaining nonseminoma cell viability and can also contribute to cisplatin resistance. Our finding of phosphorylated IGF1R in nonseminoma cells and high IGF1R expression levels in patient samples fits with previous observations noting high serum levels of IGF-2 and IGFBP2 in nonseminoma patients that reduced after treatment [42]. Similarly, the proportion of cleaved IGFBP3 (which promotes proliferation in breast cancer [43]) is greater in nonseminoma patients and declines upon response to treatment.…”
Section: Discussionsupporting
confidence: 91%
“…55,56 The inverse relationship between IGFBP-2 and IGFBP-3 expression at tissue and serum levels in a variety of cancers, including prostate, 31,55,57 ovarian, 58 and testicular cancer, has been well recognized. 59 We also found a relatively inverse relationship between secreted levels of IGFBP-2 and IGFBP-3 in lung adenocarcinoma cell lines (unpublished data). Remarkably, IGFBP-2 is predominantly expressed in cytoplasm and nucleus of lung epithelium when exposed to hyperoxia, whereas IGFBP-3 is localized in the extracellular compartment.…”
Section: Discussionmentioning
confidence: 58%
“…TGCTs frequently retain this loss of imprinting, expressing IGF2 biallelically (Van Gurp et al ., ), which has been linked to increased tumour aggressiveness in other cancer types (Damaschke et al ., ). Increased serum levels of IGF2 and IGFBP2 have been found in non‐seminomatous TGCT, decreasing upon successful therapy and increasing again in cases of recurrence (Fottner et al ., ). Our group has recently shown that IGF1R is expressed in approximately half of non‐seminomas and influences survival of non‐seminoma cells in vitro (Selfe et al ., ).…”
Section: Role Of Igf System In Oncogenesismentioning
confidence: 97%